The relation between self-efficacy, injury and fear of injury among elite athletes - McCaffrey, A.; Mrazik, M.; Klassen, R. (British Journal of Sports Medicine, 2014)
Background: A growing body of research recognizes the significance of the psychological response to injury among athletes. Yet, to date there is paucity of research that conceptualizes the role which self-efficacy plays in an athlete's response to injury (Wiese-Bjornstal, 2010; Feltz et al., 2008). Objective: To analysis the hypothetical relation between the types of injuries and the level of self-efficacy and fear to avoid future injuries. Design: Quantitative retrospective survey style for correlational and regression analysis. Setting: Elite male athletes in the Canadian Football League (CFL) at preseason training. Participants: 365 pre-season survey reports from CFL players, convenience sampling. Risk factor assessment: Measures included a self-report measure of self-efficacy (measuring fears around injuries, perceptual control of injuries, and self-efficacy to avoid injuries) and a structured report of the frequency, severity and location of injuries sustained by the athlete in a playing season. Main outcome measurements: Two main hypotheses were set out before the analysis. First was that injuries would relate to an athlete's level of self-efficacy to avoid injuries in a negative direction. Second was that fears of injuries and perceptual control of injuries could predict an athlete's level of self-efficacy. Results: Our results demonstrated significant correlations between self-efficacy to injury frequency, severity, and fears of re-injury. Regression analysis revealed variables (injuries, fear of injuries and perceptual control) significantly predict self-efficacy. Results also demonstrate that the location of injury also significantly impact levels of self-efficacy. Conclusions: This study builds on the research of understanding how athletes are affected by injuries psychologically and how they can deal with the fears and anxieties due to injuries. Practically these results, with the amounting research, can help medical and psychological treatments in dealing with an athlete's self-efficacy and fears.